Dealing with interests, values and knowledge in managing risk Workshop proceedings, Brussels, Belgium, 18-21 November 2003. (Radioactive waste management (OECD Nuclear Energy Agency), 2004)
Radioactive waste management is an area of public interest in which stakeholder involvement has largely proven itself to be beneficial to all parties and processes concerned. With growing experience, sharing best practice can be useful at the international level. These workshop proceedings deal with the local partnership methodology employed in Belgium in order to develop an integrated proposal to the national Government to construct and operate a disposal facility for low-level radioactive waste that is adapted to local conditions. The partnerships are formed amongst representatives of local organisations in affected communities and representatives of the Belgian National Radioactive Waste Management Agency.